Secure dynamic event-triggering control for consensus under asynchronous denial of service - Amini, Amir; Mohammadi, Arash; Hou, Ming; Asif, Amir (Frontiers in Computer Science, 2024)
This article proposes a secure implementation for consensus using a dynamic event-triggered control (DETC) scheme for general autonomous multi-agent systems (MAS) under asynchronous (distributed) denial of service (DoS) attacks. The DETC scheme is employed to reduce the control updates for each agent. The asynchronous DoS attacks can block each communication channel independently in an unknown pattern. Depending on the impact of DoS on the communication topology, the attacks are categorized into (i): connectivity-preserved DoS (CP-DoS) and (ii): connectivity-broken DoS (CB-DoS). In CP-DoS, the operating communication topology remains connected. On the other hand, in CB-DoS the adversary breaks the communication graph into isolated sub-graphs. To guarantee consensus under both the CP-DoS and CB-DoS, a linear matrix inequality (LMI) based optimization approach is proposed which simultaneously designs all the unknown DETC parameters as well as the state feedback control gain. The optimization is based on the weighted-sum approach and increases the minimum inter-event interval (MIET) between consecutive control updates. The trade-off between relevant features of the MAS, namely the consensus convergence rate, intensity of control updates, and level of resilience to DoS can be handled by the proposed optimization. Simulation results quantify the effectiveness of the proposed approach.